Exploring interactions between shading and view using visual difference prediction - Stephen Wasilewski; Marilyne Andersen (Buildings & Cities, 2025)
For a given view content, how well a view can be seen through different facade layers, or ‘view visibility’, depends on both the properties of the facade and the incident lighting. This dependency makes view visibility challenging to measure and quantify, which makes it difficult to understand how the benefits of a view through a window may be preserved by partially occluding facade layers. With the objective of relating the optical properties of different dynamic shading systems to what will be visible through these systems, this paper leverages existing vision models to synthetically analyse a range of facade and view scenarios. The primary outcome is that one such model, the HDR-VDP-3, usefully responds to the scenarios tested. The response is as expected for parameters with known impacts on visibility, such as direct and diffuse transmission, and free viewing area. It is also sensitive to view features such as high-contrast edges, low-contrast details and composition. Moving forward, these findings should be used to confirm the fundamental attributes of human visual perception across shading systems and, relying on human subjects, calibrate them to models’ responses. This can help guide future research into preserving the ‘key’ qualities of a view. Practice relevance Alongside visual comfort and the non-visual health effects of light, recent research has shown that views to the outside are an important aspect of daylight, joining the traditional understanding of daylight as a source of illumination. Because of the myriad demands placed on building facades, performance trade-offs are often necessary. Therefore, when evaluating dynamic facade systems, it is important to have a means of evaluating how well the system balances these aspects, including thermal performance, daylight availability, glare and view. This paper is an exploration of how to approach the characterisation of view clarity through different facades as a function of both the facade and the view itself. While the findings are preliminary, there is already an indication that the type of view content matters to how well people will see through different systems, an important consideration when planning mock-ups and selecting shade fabrics, blinds or electrochromic glazing.